Knowledge Assessment and Patient Counseling on Diabetic Foot Care - C V, Bijoy; B, Feba; R C, Vikas; C, Dhandapani; K, Geetha; A, Vijayakumar (Indian Journal of Pharmacy Practice)
Diabetic foot is a chronic complication as a result of poor diabetic control measures. Foot complications in diabetes are one of the main reasons for leg or toe amputation. The education of patient is extremely important to reduce the risk factors for lower extremity complications. The study Protocol was approved by Institutional Review Board of Kovai Medical Center and Hospital, Coimbatore. Patient knowledge regarding diabetic foot care was assessed by a structured questionnaire and categorized as good, satisfactory and poor depending upon the score. If the score was more than 70%, it was considered as good, 50- 70% as satisfactory and less than 50% as poor knowledge about foot care. Patient counselling on diabetic foot care was given to satisfactory and poor knowledge patients. Outcome of counselling was assessed through post questionnaires. About 28% patients had good knowledge, 29.3% had satisfactory knowledge and 42.7% had poor knowledge about foot care. Literacy status and income of patients had significant association with knowledge (p-value<0.001),(p-value<0.001) regarding foot care. Sex, age and history of foot infections had shown no significant statistical association. Patient counselling effectiveness was assessed and had highly significant (p=0.0001) improvement in knowledge. The awareness and attitude regarding the diabetic foot care is poor among the diabetic patients. Through the well structured foot care education by a clinical pharmacist have a significant impact in the prevention of recurrent foot infections and complications which may lead to amputation due to the lack of diabetic foot care knowledge.